Hubungan Pengetahuan Mahasiswa Keperawatan Tentang Perawatan Paliatif dan Sikap Terhadap Perawatan di Akhir Hidup - Korengkeng, Chiesa Grasiela; Rantung, Gilny Aileen Joan (Fakultas Ilmu Keperawatan Universitas Klabat, 2024)
Palliative care, as an approach that enhances the quality of life for patients with life-threatening diseases, requires deep understanding and a positive attitude from nursing students. It prevents and alleviates suffering through early identification, assessment and appropriate treatment of pain and other problems, whether physical, psychosocial or spiritual. This study aims to examine the relationship between the knowledge and attitudes of nursing students towards palliative care. The method used is a cross-sectional descriptive design with a sample of nursing students from Universitas Advent Indonesia. This study involved 93 respondents selected through convenience sampling technique. The instruments used are the validated Palliative Care Quiz for Nursing (PCQN) and Frommelt Attitudes Towards Care of the Dying (FATCOD) questionnaires. Data analysis was conducted using descriptive statistics and chi-square test with SPSS version 26. The results show that the majority of students have good knowledge of palliative care and a positive attitude towards end-of-life care. Bivariate analysis reveals a significant relationship between knowledge and attitudes towards palliative care (p=0.012). These findings affirm the importance of integrating palliative care education into the nursing curriculum to prepare nurses with adequate knowledge and positive attitudes. This study has implications for nursing education in enhancing the quality of palliative care education and suggests further research with a broader sample to generalize the results. Perawatan paliatif, sebagai pendekatan yang meningkatkan kualitas hidup pasien dengan penyakit yang mengancam kehidupan, memerlukan pemahaman mendalam dan sikap positif dari calon perawat. Penelitian ini bertujuan untuk mengkaji hubungan antara pengetahuan dan sikap mahasiswa keperawatan terhadap perawatan paliatif. Metode yang digunakan adalah desain deskriptif cross-sectional dengan sampel mahasiswa keperawatan dari Universitas Advent Indonesia. Penelitian ini melibatkan 93 responden yang dipilih melalui teknik convenience sampling. Instrumen yang digunakan adalah kuesioner Palliative Care Quiz for Nursing (PCQN) dan Frommelt Attitudes Towards Care of the Dying (FATCOD) yang telah divalidasi. Analisis data dilakukan dengan statistik deskriptif dan uji chi square menggunakan SPSS versi 26. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa memiliki pengetahuan yang baik tentang perawatan paliatif dan sikap positif terhadap perawatan di akhir hidup. Analisis bivariat menunjukkan adanya hubungan yang signifikan antara pengetahuan dan sikap terhadap perawatan paliatif (p=0,012). Temuan ini menegaskan pentingnya integrasi pendidikan perawatan paliatif dalam kurikulum keperawatan untuk mempersiapkan perawat dengan pengetahuan yang memadai dan sikap yang positif. Penelitian ini memberikan implikasi bagi pendidikan keperawatan dalam meningkatkan kualitas pendidikan perawatan paliatif, serta menyarankan penelitian lebih lanjut dengan sampel yang lebih luas untuk menggeneralisasi hasil.